Mechanical properties of supersonic-impacted Al6061 powder particles. (October 2019) - Flanagan, Tyler J.; Bedard, Benjamin A.; Dongare, Avinash M.; Brody, Harold D.; Nardi, Aaron; Champagne, Victor K.; Aindow, Mark; Lee, Seok-Woo
Abstract: The cold spray process utilizes a high-pressure gas jet to accelerate metallic particles to supersonic velocities, causing bonding to the substrate upon impact. The mechanical characterization of impacted particles is of great interest as their mechanical properties are strongly related to those of bulk cold-sprayed coatings. Here, in-situ micro-compression and tension results are presented from impacts in single-pass cold spray trials of as-atomized and heat-treated Al6061 powders. The effects of powder microstructure on the yield strength and ductility of individual impacts are discussed. Such observations contribute to a more fundamental understanding of the mechanical behavior of impacted metallic materials. Graphical abstract: Unlabelled Image